Aneurysm of the Left Portal Branch - Martínez, Diego (Eur J Case Rep Intern Med, 2018)
We describe the incidental finding of an aneurysm of the left branch of the portal vein in a patient without liver pathology. The diagnosis was confirmed by Doppler ultrasound. LEARNING POINTS: Portal vein aneurysms are rare but have been described in patients with cirrhosis and portal hypertension. In most cases they are stable and do not progress. However, they do require follow-up in case serious complications develop.